Interrogating history : essays for Hermann Kulke - Brandtner, Martin; Brandtner, Martin; Kulke, Hermann (Manohar Publ. & Distributors, 2006)
Felicitation volume to Hermann Kulke, b. 1938, former Professor of Asian History, University of Kiel; contributed articles; with special reference to Orissa State, India